Ideberg type III glenoid fractures are caused by indirect force: A report of four cases. (December 2020) - Toru, Matsugaki; Hideaki, Shibata; Tsunemasa, Matsubara
Abstract: Ideberg type III glenoid fractures are relatively rare, and the mechanisms of injury and treatment strategies remain controversial. We reviewed the fracture patterns and final radiological findings in four cases. All fractures were wider on the medial side than on the side of the articular surface. All patients had multiple ipsilateral rib fractures; three out of four patients had a concomitant acromion fracture. Therefore, the mechanism of injury for the fracture is assumed to be external force applied in the caudal direction to the medial side of the body of the scapula. The superior shoulder suspensory complex was disrupted in most cases. A good clinical outcome was obtained in two patients with percutaneous screw fixation for the glenoid fracture and rigid plate fixation for the acromion fracture and in one patient who did not have an acromion fracture. However, one patient who did not undergo fixation of the acromion fracture developed osteoarthrosis of the shoulder joint. In this type of fracture, it is important to stabilize the acromion fracture at the same time as fixation of the glenoid fracture.